BUKBER (BULAN KITA BERBAGI) PADA MASA PANDEMI COVID-19 DI KOTA METRO - Uswatun Hasanah; Revina Rizqiyani; Aulia Rahma; Kisno Kisno; Lia Ricka Pratama; Suryadi Suryadi; Alimudin Alimudin; Siti Kurniasih; Annisa Herlida Sari; Nihwan Nihwan (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2021)
The coronavirus (Covid-19) was first discovered in Wuhan, China which began to spread to various countries in the world. One of the affected countries is Indonesia. Social awareness needs to be done in the face of this pandemic. Social care is a form of attitude and action that reflects concern for others. The purpose of this paper is to describe service activities through sharing love from an early age in the month of Ramadan through storytelling, reading books, singing, and sharing several health facilities in preventing covid-19, masks, socks, and takjil. Education for early childhood is very important because that is when mental and character formation begins.